The Use of TikTok as a Literacy Learning Medium for Elementary School Students - Valentina Retna Rahayu (Indonesian Journal of Multidisciplinary Science, 2022)
Low interest in reading, writing, and talking to elementary students is the root cause that makes students not achieve. Especially in the age of technology like today, students must have hp based on android, but the utilization is still limited to having fun playing TikTok and playing games. The purpose of this study is to describe the use of TikTok as a learning medium for literacy of grade VI elementary school students and to know the responses of learners to the use of TikTok as a learning medium for literacy of grade VI elementary school students. This study uses qualitative descriptive research methods, data collection techniques using observation methods, interviews, documentation, and questionnaires with research subjects in 23 students of 6th grade of SDN Benchmark 1 District Kraksaan, Probolinggo. The results of this study show that the TikTok application can be used as a medium that supports the learning process of literacy of grade VI elementary school students, and the utilization of TikTok application as a learning medium obtained positive responses of learners on literacy learning of class VI students in elementary school.